(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
A comparative analysis of the improved power quality HF isolated transformer AC-DC buck converters has been made to present a detailed exposure on their various topologies. The detailed classification of these AC-DC boost converters have 4 categories with number of circuits and concepts has been carried out to provide easy selection of proper topology for a specific application. These AC-DC converters provide a high level of power quality at the AC mains, well-regulated and also free ripple isolated DC outputs. Moreover, these converters have been operated very satisfactorily with very wide AC mains voltage and frequency variations resulting in a concept of universal input..